2015
DOI: 10.1007/s10616-015-9879-4
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour action on human glioblastoma A1235 cells through cooperation of bee venom and cisplatin

Abstract: Cisplatin (cDDP) is one of the most widely used anticancer-drugs in both therapy and research. However, cDDP-resistance is the greatest obstacle for the successful treatment of cancer patients. In the present study, the possible joint anticancer effect of bee venom (BV), as a natural toxin, and cDDP towards human glioblastoma A1235 cells was evaluated. Treatment with BV alone in concentrations of 2.5-30 μg/ml displayed dose-dependent cytotoxicity towards A1235 cells, as evaluated with different cytotoxicity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Many in vitro and in vivo studies indicated that HBV has a direct antitumor effect and leads to inhibition of proliferation, metastasis, angiogenesis, and induction of apoptosis 1 , 25 . Moreover, some promising findings suggested that HBV can be used in combination with standard chemotherapy, e.g., cisplatin 26 , 27 . Another important application of HBV is venom immunotherapy, which is an effective treatment of severe honeybee sting-induced allergic reactions 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Many in vitro and in vivo studies indicated that HBV has a direct antitumor effect and leads to inhibition of proliferation, metastasis, angiogenesis, and induction of apoptosis 1 , 25 . Moreover, some promising findings suggested that HBV can be used in combination with standard chemotherapy, e.g., cisplatin 26 , 27 . Another important application of HBV is venom immunotherapy, which is an effective treatment of severe honeybee sting-induced allergic reactions 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Bee venom makes sense as a complement to cisplatin: it has protective effects in many areas of the body such as the blood and nerves [ 6 ]; it is able to inhibit cell growth in tumours [ 7 ]; and has even been examined and used in complementary treatments that are necessitated by the effects of chemotherapy, such as allodynia [ 8 ] and neuropathy [ 9 ]. Cisplatin in combination with bee venom has been successfully used against human cervical and laryngeal carcinoma cells, including their drug-resistant sublines [ 10 ], and human glioblastoma [ 11 ]. Several studies have found that phospholipase A 2 , another component of bee venom, not only mitigates the negative impact of cisplatin on kidneys [ 12 ], but also boosts regulatory T cell (Treg) numbers in the spleen and enhances Treg traffic to the kidneys following cisplatin exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the promising properties that are attracting much interest from pharmacological and biotechnological fields, MLT (whose initial structure is helical, when embedded in a lipid bilayer) can change to a dimeric form that destabilizes and alters artificial lipid bilayers containing dioleoylphosphatidylcholine (Somwongin et al, 2018). Therefore, MLT may induce morphologic changes in a dose-dependent manner, being a nonselective cytolytic peptide that may induce the lysis of red blood cells and human peripheral blood lymphocytes, among others (Gajski et al, 2016). Indeed, while in small doses MLT has antiinflammatory effects, increases capillary permeability, in higher doses it may cause inflammation, itching, irritation and local pain (Lee and Bae, 2016).…”
Section: Bioactive Compounds Of Bee Venom and Their Biological Effectsmentioning
confidence: 99%
“…Phospholipase A 2 has been reported to be the most abundant enzyme of BV, corresponding to 10-12% of its dry weight matter (dos Santos-Pinto et al, 2018). Due to its high molecular weight and strong antigenicity, this enzyme has been pointed as the major cause of the systemic allergic reactions to BV (Gajski et al, 2016;Hossen et al, 2016). On the other hand, several recent reports unveiled the potentiality of PLA 2 in the treatment of human disorders (Table 1) including Parkinson's disease, asthma, several types of cancer, as well as immune mediated disorders like cisplatin-induced nephrotoxicity, hepatotoxicity and Lupus nephritis (Ratcliffe et al, 2014).…”
Section: Phospholipase a 2 (Ec 3114)mentioning
confidence: 99%